Elements of environmental chemistry - Hites, Ronald A.; Raff, Jonathan D. (Wiley, 2012)
Summary: "Tutorial in style, this book fully incorporates real-world problems and extensive end-of-chapter problem sets to immerse the reader in the field. Chapters cover mass balance, chemical kinetics, carbon dioxide equilibria, pesticide and structures and much more. Extensively revised, updated, and expanded, this second edition includes new chapters on atmospheric chemistry, climate change, and polychlorinated biphenyls and dioxins, and brominated flame retardants. In addition, new practice problems and a helpful tutorial on organic chemistry names and structures have been added to improve both the scope and accessibility of the book."--Provided by publisher